2020
DOI: 10.1021/acsomega.9b03346
|View full text |Cite
|
Sign up to set email alerts
|

Novel MoS2–DOPO Hybrid for Effective Enhancements on Flame Retardancy and Smoke Suppression of Flexible Polyurethane Foams

Abstract: A novel MoS2–DOPO hybrid has been successfully synthesized through the grafting of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) on the surface of MoS2 nanosheets using allyl mercaptan as an intermediate. MoS2–DOPO was used as a flame retardant additive to prepare flame-retardant flexible polyurethane foam (FPUF). The influence of MoS2–DOPO on the mechanical, thermal stability, and flame retardancy properties of FPUF composites were systematically investigated. The incorporation of MoS2–DOPO could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…The modified MoS 2 has shown great flame resistance and smoke suppression in polyurethane foam but is yet to be tested on yarn or fabric. 70…”
Section: Fire Protection/retardant Activitymentioning
confidence: 99%
“…The modified MoS 2 has shown great flame resistance and smoke suppression in polyurethane foam but is yet to be tested on yarn or fabric. 70…”
Section: Fire Protection/retardant Activitymentioning
confidence: 99%
“…reported that the application of natural and synthetic polymer materials is one of the causes of frequent fires. Polymers with improved flame retardancy have received great attention in the industry. At present, flame retardants containing elements such as phosphorus, nitrogen, and halogen are being widely studied and applied. However, flame retardant polymeric materials containing halogens produce a large amount of toxic smoke during combustion. This seriously harms the environment and people’s health.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, phosphorus-containing flame retardants, especially 9,10dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and its derivatives, have attracted much attention (Huo et al, 2020;Huo et al, 2021). 9,10-Dihydro-9-oxa-10-phenanthrene-10oxide (DOPO) and its derivatives were used to improve their use as flame retardants, as these have higher thermal stability, excellent flame retardancy, and low toxicity (Ma et al, 2020;Zhi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%